STUDI MODEL PENGARUH PERUBAHAN JUMLAH PENDUDUK TERHADAP PENGGUNAAN LAHAN DI KOTA METRO TAHUN 2010-2020 - Risky, M; Malik, IB Ilham; Saraswati, Zenia F (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
Every year, Metro City sees a rise in population, which has an impact on how the city uses its property. One of the cities in Lampung Province with a total area of 7315.40 hectares is Metro City. Given that this territory makes up only 0.22 percent of Lampung Province's total area, there is concern that Metro City may face issues as its population grows and its need for land increases while its supply does not.. By adopting a guided categorization approach to define the Metro City's land use area, the land use is divided into three categories: the use of developed land, the use of undeveloped land, and the use of water bodies. A supervised classification analysis was utilized to identify the land use in Metro City, and a straightforward linear regression analysis was employed to ascertain the connection between population and land use in Metro City. In the years 2010 to 2020, Metro City's population grew by 23,205, while in the same period, the amount of developed land in Metro City climbed by 429.72 hectares. The North Metro District, which has an area of 156.94 hectares, had the subdistricts that underwent the greatest changes in land use from undeveloped land use to the most extensive use of built up land, while the South Metro subdistrict, which has an area of only 48.53 hectares, underwent the fewest changes. If the population is compared to the use of undeveloped land, the relationship is inverse; for every rise in population, the use of undeveloped land will suffer a decrease. However, there will be an increase in the use of built-up land for every increase in population.